ANALISIS IMPLEMENTASI ACTIVITY BASED COSTING (ABC) UNTUK MENENTUKAN BEBAN POKOK PRODUKSI PADA RAMAYANA BAKERY - Anisa Karunia Putri; Istiarto Istiarto; I Made Suarta (Sekolah Tinggi Ilmu Ekonomi AMM, 2018)
This research is a qualitative descriptive research at Ramayana Bakery. This research has three main objectives. First, it aims to know the calculation of the cost of goods manufactured with the traditional system is used by the company. Second, to know the calculation of cost of goods manufactured with activity based costing method. Third, to know comparison the calculation of cost of goods manufactured by using traditional system and activity based costing method at company. Data collection methods used in this research are interviews, documentation and observation. Objects in this research are costs incurred in baking bread at Ramayana Bakery such as raw material cost, direct labor cost, and factory overhead cost. There is a difference in the results of the calculation of the cost of goods manufactured between traditional systems and activity based costing. This is due to the activity that is chosen as a cost driver in the traditional system is much more used for roti sisir, roti moka, roti tawar, and roti creamball than to roti bluder, roti isian coklat and roti isian strawberry. Roti bluder, roti isian coklat and roti isian strawberry use other activities more dominantly and the activity is not used as a basis in traditional systems. In the end, the cost of goods manufactured for roti sisir, roti moka, roti tawar, and roti creamball become overcost and roti bluder, roti isian coklat and roti isian strawberry also becomes under cost.